The PPARGC1A Gly482Ser polymorphism is associated with elite long-distance running performance. Issue 1 (2nd January 2023) - Hall, Elliott C.R.; Lockey, Sarah J.; Heffernan, Shane M.; Herbert, Adam J.; Stebbings, Georgina K.; Day, Stephen H.; Collins, Malcolm; Pitsiladis, Yannis P.; Erskine, Robert M.; Williams, Alun G.
ABSTRACT: Success in long-distance running relies on multiple factors including oxygen utilisation and lactate metabolism, and genetic associations with athlete status suggest elite competitors are heritably predisposed to superior performance. The Gly allele of the PPARGC1A Gly482Ser rs8192678 polymorphism has been associated with endurance athlete status and favourable aerobic training adaptations. However, the association of this polymorphism with performance amongst long-distance runners remains unclear. Accordingly, this study investigated whether rs8192678 was associated with elite status and competitive performance of long-distance runners. Genomic DNA from 656 Caucasian participants including 288 long-distance runners (201 men, 87 women) and 368 non-athletes (285 men, 83 women) was analysed. Medians of the 10 best UK times (Top10) for 10 km, half-marathon and marathon races were calculated, with all included athletes having personal best (PB) performances within 20% of Top10 (this study's definition of "elite"). Genotype and allele frequencies were compared between athletes and non-athletes, and athlete PB compared between genotypes. There were no differences in genotype frequency between athletes and non-athletes, but athlete Ser allele carriers were 2.5% faster than Gly/Gly homozygotes ( p = 0.030). This study demonstrates that performance differences between elite long-distance runners are associated with rs8192678 genotype, with the Ser allele appearing to enhance performance.